A Guide to Early Modern French Louisiana Sources. Issue 3 (June 2015) - Lamotte, Mélanie
Recent decades have witnessed steady and significant historiographical interest in the history of early modern French Louisiana. The field presently boasts a dynamic set of analysts actively investigating primary sources across America and France. In addition, many French Louisiana sources and historical issues remain unexplored, thereby suggesting that the historiography of early modern French Louisiana will continue to grow substantially. While numerous inventories of Louisiana sources have been published, few have specifically focused their attention on early modern French Louisiana documents. Several of these guides contain information that is no longer valid by pointing to sources that have been moved or have subsequently disappeared. In addition, many sources are being made more readily available through digitization and the creation of online databases. This article provides much-needed guidance on identifying and using French Louisiana sources. It lists the sources available and investigates their nature, details of access, state of preservation, as well as their state of digitization. It also suggests potential uses and interpretations that might be gleaned from such source material.